Effectiveness of Non-Governmental Organizations in Rural Development in Chitral District, Khyber Pakhtunkhwa Province of Pakistan - Mujahid Shah, Anwar Ul (Universiti Malaysia Sarawak (UNIMAS), 2018)
The present study has been focusing towards determining the effectiveness of the NGOs in making a difference in the development of Pakistan rural areas particularly considering Chitral province from the community approach. This research intended to examine how NGOs in Chitral apply community approach for the rural development of Chitral particularly by focusing on Ayun and Yarkhun Union Councils. The present research used a case study research design and ethnographic qualitative approach by focusing on the directly observable material items to notice the entire education, health and gender equality in Chitral after the entry of NGOs. In order to collect appropriate data, three key tools were selected, including observations, Focus Group Discussion (FGD), and In-depth Interviews (IDI). Purposive sampling method was used to select a total of 152 informants from the two councils of Chitral, Ayun, and Yarkhun for data collection where 64 informants from each council were selected for FGDs and 12 for IDIs. The number of the sample was subject to saturation point. The snow ball sampling was used to reach out the various informants in the study. The data were analyzed using open coding method and thematic analysis. The results of the study have indicated that the NGOs (particularly AKRSP and SRSP functioning in Ayun and Yarkhun Councils of Chitral, respectively) are primarily applying community approach by focusing on different factors. For instance, the major ways or activities followed to implement community approach within the identified regions are involving local people and staff members in every activity and/or even in decision-making process to know about their needs. NGOs in Chitral have been trying to make education compulsory for both genders, besides improving health awareness and facilities in the hospitals, and promoting gender equality through effective actions, including campaigns and workshops. The research further explored that the activities iv adopted by NGOs in these councils assessed by the communities were found to perform effectively in informing people regarding the importance of high education, improved health and gender empowerment without which the rural development (high standard of living) is not possible. The study depicted that the entry of NGOs in Chitral has been accepted through implementing projects, which are influential in making significant contributions to bring positive changes to the communities. Thus, these organisations are suggested to take some rational actions to aware people through cost-benefit analysis who are less interested in participating the rural development. The research had indicated that for the issues encountered in the case of community approach, awareness and understanding should be increased for rural development in a more holistic way. On the contrary, the contemplated study further showed some research limitations, such as lack of mixed method. Thus, it is recommended for future researchers to employ a mixed method on a similar study.